Awareness of gestational diabetes problem among Sohag Governorate women - Hamdy Saad; Adel Abdel Aziz; Eslam Emad; Mahmoud Gaber (SpringerOpen, 2023)
Abstract Background Gestational diabetes mellitus (GDM) is the most frequent and prevalent medical condition in pregnancy. Well-controlled GDM results in reduction of these unfavorable outcomes. Aim To assess women's knowledge of many elements of gestational diabetes mellitus, including general awareness of the condition, risk factors, diabetic patients' diets, and consequences among the women in the governorate of Sohag. Patients and methods In this research, 500 women were chosen at random from a population, over a period of 6 months, to participate in a descriptive survey utilizing a questionnaire approach in Sohag Governorate. Results The mean total knowledge score was 9.62 ± 4.24. A total of 69.6% of study participants showed good knowledge (≥ 9), while 30.4% of them showed low knowledge about gestational diabetes. There was significant positive relation between degree of knowledge and family history of diabetes (p = 0.038) as there was substantial increase of high knowledge score in cases who had positive history of family history of diabetes. Conclusion Awareness about gestational diabetes mellitus was satisfactory among women in Sohag Governorate. Other's experiences or advices were the most common source of general knowledge. There was significant proportional relationship between degree of awareness and occupation, higher age, family history of diabetes, history of gestational diabetes, and level of education. Healthcare workers have to play a greater role in awareness about GDM among women. Trial registration Awareness of gestational diabetes problem among Sohag Governorate women, NCT05148897. Registered 10 November 2021,  https://register.clinicaltrials.gov/prs/app/action/LoginUser?ts=2&cx=-jg9qo3 .